Intervention Supportive Educative System Based on Self Care and Family Centered Nursing Model to Family Support in Teaching Cough Ethics and Correct Sputum Disposal of TBC Patients at Sanggau Ledo Health Center, Bengkayang District - Tri Wahyuni; Parliani; Cau Kim Jiu; Kharisma Pratama; Tutur Kardiatun; Sukartina (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Tuberculosis is an infectious disease that attacks the lungs characterized by granuloma formation and causes tissue necrosis, a direct infectious disease caused by the TBC germ (mycobacterium tuberculosis). Problems that often arise in tuberculosis sufferers are about knowledge, activities and psychosocial family support. Purpose: this study was to determine a supportive educative system intervention based on self-care and family centered nursing models for family support in teaching cough and sputum disposal properly. Methods: The research design used was quantitative with a Quasi Experimental design pre-test post-test without control group. The sample in this study was 20 samples taken before and after the intervention. Results: based on the bivariate analysis of knowledge, activity, and family support with the Wilcoxon test, it shows that in the intervention group after education, this self-care based system affects people with tuberculosis, the variable knowledge with p value 0,000, activity (behavior) with p value 0,000 and family support p. value 0.050, which means p value <α 0.050, this study shows that there is a difference in scores of supportive educative system interventions based on self-care and family centered nursing models on family support in teaching cough and sputum disposal properly. Suggestion: This study recommends that poly pulmonary health services provide a supportive educative system intervention based on self-care and family centered nursing models for family support in teaching cough and sputum disposal in TBC patients.